2013
DOI: 10.1116/1.4790865
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electrical characterization of InN, InGaN, and p-InGaN grown by metal-modulated epitaxy

Abstract: InN, high indium content InGaN, and Mg-doped InGaN were grown by metal modulated epitaxy (MME). Transient reflection high-energy electron diffraction intensities were analyzed during the growth of InN and found to be similar to that previously reported for GaN and AlN. The x-ray diffraction rocking curve and background electron concentration of InN grown by MME were found to be respectable in comparison to recent reports in literature. InGaN alloys grown by MME were also investigated, and a method for detectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 46 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…The nitrogen plasma resulted in a beam equivalent pressure of ∼2.2 × 10 –5 Torr. The MME technique, as described in detail in previous works by this research group, was employed for the growth of each GaN film reported here. , RHEED was used for surface level in situ monitoring of the homoepitaxial GaN films during growth. A Philips X’Pert Pro MRD was used for post-growth XRD of the grown films.…”
Section: Methodsmentioning
confidence: 99%
“…The nitrogen plasma resulted in a beam equivalent pressure of ∼2.2 × 10 –5 Torr. The MME technique, as described in detail in previous works by this research group, was employed for the growth of each GaN film reported here. , RHEED was used for surface level in situ monitoring of the homoepitaxial GaN films during growth. A Philips X’Pert Pro MRD was used for post-growth XRD of the grown films.…”
Section: Methodsmentioning
confidence: 99%
“…Desorption of InN is critical at raised temperatures because indium will evaporate from the sample surface. To retain indium in the nanorods, the metal-modulated epitaxy (MME) technique was utilized [67,68]. MME involves periodic opening and closing of the metal shutters in order to modulate the metal fluxes, while the N 2 shutter is kept open.…”
Section: Growth Techniquementioning
confidence: 99%
“…23,24 However, many research groups reported that the formation of highly crystalline InN NWs is difficult, notably because of the segregation phenomenon and easy desorption of In atoms from the NW surface. [25][26][27] As a result, self-powered TFSs fabricated with semiconductor III-nitride NWs have not been reported yet.…”
Section: Introductionmentioning
confidence: 99%